The Efficient use of Human Resources in the Digital Economy - Ulugmuradova Nodira Bedimuradovna (Research Parks Publishers, 2021)
The article is devoted to the peculiarities of the functioning of the labour market in the context of the development of the digital economy and the determination of the main directions in the management of processes related to the accumulation and use of human capital as the main factor of production in the context of digitalization.